Chrono-communication and cardiometabolic health: The intrinsic relationship and therapeutic nutritional promises - Senesi, Pamela; Ferrulli, Anna; Luzi, Livio; Terruzzi, Ileana (Frontiers in Endocrinology, 2022)
Circadian rhythm, an innate 24-hour biological clock, regulates several mammalian physiological activities anticipating daily environmental variations and optimizing available energetic resources. The circadian machinery is a complex neuronal and endocrinological network primarily organized into a central clock, suprachiasmatic nucleus (SCN), and peripheral clocks. Several small molecules generate daily circadian fluctuations ensuring inter-organ communication and coordination between external stimuli, i.e. light, food and exercise, and body metabolism. As an orchestra, this complex network can be out of tone. Circadian disruption is often associated with obesity development and above all with diabetes and cardiovascular disease onset. Moreover, accumulating data highlight a bidirectional relationship between circadian misalignment and cardiometabolic disease severity. Food intake abnormalities, especially timing and composition of meal, are crucial cause of circadian disruption but evidence from preclinical and clinical studies have shown as food could represent a unique therapeutic approach to promote circadian resynchronization. In this review, we briefly summarize the structure of circadian system and discuss the role playing by different molecules (from leptin to ghrelin, incretins, FGF-21, GDF15) to guarantee circadian homeostasis. Based on the recent data, we discuss the innovative nutritional interventions aimed at circadian re-synchronization and consequently to improve cardiometabolic health.